2023
DOI: 10.1097/meg.0000000000002549
|View full text |Cite
|
Sign up to set email alerts
|

Development of a risk score to predict portal vein tumor thrombosis in patients with hepatocellular carcinoma

Abstract: Background Portal vein tumor thrombosis (PVTT) is a common complication of hepatocellular carcinoma and is one of the most negative prognostic factors. The management of patients with PVTT is challenging. The aim of the study was to develop a score predictive of tumor thrombosis. Methods Data from a large cohort of 2243 hepatocellular carcinoma patients (all stages) recorded in the Progetto Epatocarcinoma Campania (January 2013–April 2021) database were analyzed. To construct the score, univariate generalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In our study, we observed that a total of 136 patients (13.3%) experienced PVTT events during the follow-up period, which was mostly in line with the results reported by Guarino et al (11.1%) and Tortora et al (14.4%). 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we observed that a total of 136 patients (13.3%) experienced PVTT events during the follow-up period, which was mostly in line with the results reported by Guarino et al (11.1%) and Tortora et al (14.4%). 24 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that a total of 136 patients (13.3%) experienced PVTT events during the follow-up period, which was mostly in line with the results reported by Guarino et al (11.1%) and Tortora et al (14.4%). 24,25 Multivariate Cox regression analysis revealed that male gender, AAPR ≤0.49, APRI >0.48, the presence of extrahepatic metastasis, and multiple tumors were independent risk factors for PVTT. We suggest that patients with a high risk of PVTT progression should be followed up regularly and closely.…”
Section: Discussionmentioning
confidence: 99%
“…Portal vein tumor thrombosis, the predominant type of macrovascular invasion, is present in approximately 10–40% of individuals diagnosed with HCC. 44 Its occurrence typically signifies accelerated disease advancement and is associated with intrahepatic and extrahepatic metastasis, portal hypertension, hepatocellular jaundice, and refractory ascites. Consequently, the ability to anticipate the development of PVTT in patients and implement timely interventions to postpone or mitigate its effects is imperative.…”
Section: Progress Of Artificial Intelligence In Imaging Prediction Of...mentioning
confidence: 99%